2012
DOI: 10.1155/2012/840737
|View full text |Cite
|
Sign up to set email alerts
|

Role of Macrophage Migration Inhibitory Factor in the Proliferation of Smooth Muscle Cell in Pulmonary Hypertension

Abstract: Pulmonary hypertension (PH) contributes to the mortality of patients with lung and heart diseases. However, the underlying mechanism has not been completely elucidated. Accumulating evidence suggests that inflammatory response may be involved in the pathogenesis of PH. Macrophage migration inhibitory factor (MIF) is a critical upstream inflammatory mediator which promotes a broad range of pathophysiological processes. The aim of the study was to investigate the role of MIF in the pulmonary vascular remodeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 41 publications
4
31
0
2
Order By: Relevance
“…Consistent with these findings, pulmonary infiltration of MCT-injected rats chronically treated with the MIF antagonist ISO-1 or with anti-CD74 neutralizing antibodies is substantially reduced. Consistent with our findings, Zhang and colleagues have also reported that MIF plays a critical role in hypoxia-induced PH and that its inhibition may be beneficial in preventing the development and progression of the hypoxic PH (38,39). In addition, Bernhagen and colleagues (9) have demonstrated that the inhibition of CD74 with neutralizing antibodies reduced the MIF-dependent monocyte arrest on ex vivo carotid arteries from apolipoprotein E-deficient (Apoe-/-) mice.…”
supporting
confidence: 89%
“…Consistent with these findings, pulmonary infiltration of MCT-injected rats chronically treated with the MIF antagonist ISO-1 or with anti-CD74 neutralizing antibodies is substantially reduced. Consistent with our findings, Zhang and colleagues have also reported that MIF plays a critical role in hypoxia-induced PH and that its inhibition may be beneficial in preventing the development and progression of the hypoxic PH (38,39). In addition, Bernhagen and colleagues (9) have demonstrated that the inhibition of CD74 with neutralizing antibodies reduced the MIF-dependent monocyte arrest on ex vivo carotid arteries from apolipoprotein E-deficient (Apoe-/-) mice.…”
supporting
confidence: 89%
“…MIF, a critical upstream regulator of inflammation, inhibits prostacyclin synthase expression in animal models of hypoxiainduced pulmonary hypertension and is associated with pulmonary artery smooth-muscle cell proliferation. 24,25 Studies involving other diseases have also shown that MIF can activate aromatase and increase estradiol levels. 26 Additionally, MIF has been implicated in the pathogenesis of several autoimmune diseases, including autoimmune liver disease, [27][28][29][30] which is a known risk factor for POPH.…”
Section: Discussionmentioning
confidence: 99%
“…In endothelial cells, a MIF-CD74 interaction can lead to the activation of Src-family kinase, MAPK/ERK, PI3K/Akt and NF-κB pathways, and to apoptotic resistance via elevated BCL2 and BCL-xL and repressed p53 38-43 . In addition, MIF can bind to CXCR2 and CXCR4 and lead to the proliferation of pulmonary artery smooth muscle cells and contribute to hypoxic PH 44-47 . In addition to elevated production of cytokines and chemokines, phenotypic alterations and functional defects in cytotoxic T and natural killer (NK) cells are linked to human PAH and experimental PH as well as pulmonary veno-occlusive disease 48, 49 .…”
Section: Chemokines Cytokines and Pulmonary Arterial Hypertensionmentioning
confidence: 99%